2018
DOI: 10.1108/lhs-03-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

A model for measuring effectiveness of quality management practices in health care

Abstract: Purpose Health care is an example of an organization where the needs of potential clients are much greater than the capabilities of the service delivery system. The implementation of any medical procedure, as well as the provision of any service, just like the manufacturing of any product, can be decomposed into a series of tasks. The purpose of this paper is to propose a model for measuring the effectiveness of quality assurance tasks in health-care delivery processes. Design/methodology/approach The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…It is the responsibility of top-management to provide continuous improvement of quality health service delivery to the patient through effective and efficient patient care and satisfactory medical services that will lead to customer retention and HCE survival (Ali and Alolayyan, 2013). Myszewski and Sinha (2018) found that poor leadership and lack of top-management commitment is one of the major barriers of QM effectiveness assurance. Weak leadership leads to defective products or services delivered and further increases inconsistencies in organization-wide policies and program (Myszewski and Sinha, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the responsibility of top-management to provide continuous improvement of quality health service delivery to the patient through effective and efficient patient care and satisfactory medical services that will lead to customer retention and HCE survival (Ali and Alolayyan, 2013). Myszewski and Sinha (2018) found that poor leadership and lack of top-management commitment is one of the major barriers of QM effectiveness assurance. Weak leadership leads to defective products or services delivered and further increases inconsistencies in organization-wide policies and program (Myszewski and Sinha, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Myszewski and Sinha (2018) found that poor leadership and lack of top-management commitment is one of the major barriers of QM effectiveness assurance. Weak leadership leads to defective products or services delivered and further increases inconsistencies in organization-wide policies and program (Myszewski and Sinha, 2018). Therefore, successful TQM arises from strong leadership and management efforts aiming to develop and communicate a strategic quality plan, building quality culture, setting quality policies and promoting continuous improvement program in the organization to facilitate employee, customer, supplier, resource and information (Mosadeghrad, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the problem identification and problem prioritization can be handled by using Pareto type analysis and its effectiveness can be examined related to the capacity and tasks for process improvement management (Myszewski and Sinha, 2018).…”
mentioning
confidence: 99%
“…One of the key premises of this research is the observation that medical services are like improvement micro-projects and that the consideration of value creation (as its measure of effectiveness) can be expressed, among others, using the model presented in Myszewski and Sinha (2018). The value is about providing and making available as many quality attributes as possible to patients within the given cost constraints and the health issue severity constraints.…”
mentioning
confidence: 99%